Self-Instruction Group Counselling Technique to Reduce Students Academic (Jurnal Bimbingan Konseling, 2018)
This study aimed to determine the impact of self-instruction group counseling technique on students' academic procrastination behavior. To achieve such objective, one-group pretest - posttest design was used in this study by involving 8 students as participants. The results of paired t-test showed that the students' academic procrastination level decreased higher in the posttest measurement (71.39%) than pretest (80.21%, t = 14.982, p < 0.01). Moreover, this study further discussed the possibility of applying self-instruction in overcoming students' academic procrastination behavior problem at State Junior High School (SMP Negeri) 11 Surakarta.